2021
DOI: 10.1111/twec.13214
|View full text |Cite
|
Sign up to set email alerts
|

The impact of free trade agreements on Middle East and North Africa exports of intermediate and final goods

Abstract: This paper is the first to analyze the impact of free trade agreements (FTAs) and the harmonization of rules of origin (RoO) on Middle East and North African (MENA) countries' exports differentiating between final and intermediate goods for a global sample of trade partners. Data on exports from four MENA countries (Egypt, Jordan, Morocco and Tunisia) to 61 destinations over the period 1995-2016 are used to estimate a structural gravity model applying a Poisson Pseudo Maximum Likelihood (PPML) estimator. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Franco‐Bedoya and Frohm (2022) noted that comprehensive trade agreements have more significant trade effects. In their recent study, Cardozo et al (2022) observed that FTAs have successfully increased MENA exports, particularly FTAs that eliminate protection on agricultural products. To foster its objective of broader trade integration, Oman also took the ambitious step to reform its trading status, which is now considered a more flexible and fast‐growing economy.…”
Section: Introductionmentioning
confidence: 99%
“…Franco‐Bedoya and Frohm (2022) noted that comprehensive trade agreements have more significant trade effects. In their recent study, Cardozo et al (2022) observed that FTAs have successfully increased MENA exports, particularly FTAs that eliminate protection on agricultural products. To foster its objective of broader trade integration, Oman also took the ambitious step to reform its trading status, which is now considered a more flexible and fast‐growing economy.…”
Section: Introductionmentioning
confidence: 99%